Fatty acid desaturase 2 promoter mutation is not responsible for Δ6-desaturase deficiency - Gregory, Melissa K (Nature Publishing Group, 2011)
Dietary essential polyunsaturated fatty acids (PUFAs) require fatty acid desaturases (FADS) for conversion to long-chain PUFAs (LCPUFAs), which are critical for many aspects of human health. A Δ6-desaturase deficiency in a single patient was attributed to an insertion mutation in the FADS2 promoter. Later population studies have shown this thymidine nucleotide (T) insertion to be a common polymorphism (rs3834458). We examined correlations between rs3834458 variants and fatty acid evidence of FADS2 activity in a cohort of rheumatoid arthritis patients selected for low or nil consumption of n-3 LCPUFA as fish or fish oil. The presence of the T allele was associated with higher FADS2 activity, as indicated by higher conversion of plasma n-3 PUFA to LCPUFA. However, the T-insertion/deletion polymorphism did not affect FADS2 promoter activity in luciferase reporter assays in HepG2 or NIH/3T3 cells. Our results indicate that the polymorphism rs3834458 does not appear to directly affect FADS2 promoter activity and is not responsible for a previously reported Δ6-desaturase deficiency.